Electrochemical nucleation and three-dimensional growth under mixed kinetic-diffusion control: analytical approximation of the current transient. (1st July 2016) - Altimari, Pietro; Pagnanelli, Francesca
Abstract: An analytical expression is derived for the current transient generated by electrochemical nucleation and three-dimensional growth of metal nanoparticles under mixed kinetic-diffusion control. The expression is the approximate solution of a novel mathematical model and describes the dependence of the current transient on nucleation rate, number density of active sites and charge transfer kinetic constant. Relative difference between the current predicted by the analytical expression and numerical solution of the original model is invariably lower than 0.1.